Toward a Social Policy for Argentina's Infrastructure Sectors: Evaluating the Past and Exploring the Future - Foster, Vivien (World Bank, Washington, D.C., 2013)
Argentina was a pioneer of infrastructure reform in the early 1990s. The social dimension of infrastructure services was typically overlooked in the reform process. However, social sensitivities often resurfaced in the years that followed, leading to a series of ad hoc social policy measures that cumulatively amount to US$200 million a year. Foster quantifies and prioritizes the social challenges faced by the Argentine infrastructure sectors, evaluates how well existing social policies are functioning, and provides illustrative simulations of how certain changes in the design of social policy could improve the performance of current social policies. The author's findings are that current social policies do not prove to be very effective in targeting resources to the poor. They have no real impact on the distribution of income across customers. An important reason for this targeting failure is the tendency to allocate resources to all households resident in a particular geographical area, irrespective of socioeconomic status. A series of simulations that limit subsidies to households reaching a minimum score on a multidimensional poverty index show that individual targeting of this kind potentially leads to a more progressive distribution of subsidies. However, the greatest improvements in targeting performance would be achieved if efforts switched from subsidizing the use of infrastructure services to subsidizing connections to those services.